2017
DOI: 10.1073/pnas.1708161114
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale characterization of the mineral phase at skeletal sites of breast cancer metastasis

Abstract: Skeletal metastases, the leading cause of death in advanced breast cancer patients, depend on tumor cell interactions with the mineralized bone extracellular matrix. Bone mineral is largely composed of hydroxyapatite (HA) nanocrystals with physicochemical properties that vary significantly by anatomical location, age, and pathology. However, it remains unclear whether bone regions typically targeted by metastatic breast cancer feature distinct HA materials properties. Here we combined high-resolution X-ray sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 45 publications
2
56
1
Order By: Relevance
“…Furthermore, the bone tropic subline of MDA-MB-231 cells showed increased secretion of pro-osteoclastic interleukin-8 in an HA-rich environment, which may therefore contribute to the vicious cycle [147]. In a recent study, the skeletal sites with less mature HA were found to be more likely to develop bone metastasis in a mouse model of breast cancer [148].…”
Section: Adaptation To the Physiochemical Properties Of Bone Environmmentioning
confidence: 99%
“…Furthermore, the bone tropic subline of MDA-MB-231 cells showed increased secretion of pro-osteoclastic interleukin-8 in an HA-rich environment, which may therefore contribute to the vicious cycle [147]. In a recent study, the skeletal sites with less mature HA were found to be more likely to develop bone metastasis in a mouse model of breast cancer [148].…”
Section: Adaptation To the Physiochemical Properties Of Bone Environmmentioning
confidence: 99%
“…Often, CTCs that survive extravasation do not immediately proliferate, but instead lay dormant for months to decades until the surrounding milieu becomes favorable for regrowth 3 , 4 . Emerging evidence suggests that metastatic relapse may not be explained solely by intrinsic genetic instability of DTCs, instead bi-directional interaction with the surrounding microenvironment needs to be considered 5 7 . Understanding how the local milieu surrounding DTCs prevents or aids in regaining proliferative phenotypes is imperative to developing better therapeutic strategies to prevent or delay lethal metastasis.…”
mentioning
confidence: 99%
“…IR-TV is an optimization problem that minimizes the objective function in Eq. (8), which consists of a Poisson likelihood ( | ) of observing the measurement given the object , and a TV regularizer…”
Section: Total-variance (Tv) Regularizationmentioning
confidence: 99%
“…Due to the high penetration depth and material-specific signatures, X-ray diffraction (XRD) is a powerful tool to probe the material properties at molecular level, such as solving the crystalline structure [1,2], identifying the chemical composition in compounds with high sensitivity [3][4][5], and more recently, diagnose structural defects in bones, prosthetic implants [6,7], or diseaserelated anomaly in soft tissues [8,9]. For heterogeneous object on the centimeter scale or larger, resolving the XRD profile of individual sample voxels requires a combination of XRD measurement and computed tomography (CT) [10], which captures the XRD signals under different projections and is termed X-ray diffraction tomography (XDT).…”
Section: Introductionmentioning
confidence: 99%